Assessment of COVID-19 Vaccine Impact on Women’s Menstrual Health within an 18-Month Follow-Up - Mona Sadat Larijani; Sana Eybpoosh; Delaram Doroud; Anahita Bavand; Ladan Moradi; Fatemeh Ashrafian; Parinaz Tajmehrabi Namini; Mahsan Zali; Amitis Ramezani (Obstetrics and Gynecology International)
Considering menstruation as a crucial factor in females’ health and fertility, any factor that could change its cycle is important. This study was conducted from April 2021 to October 2022 on females who got 3 doses of vaccines against SARS-CoV-2 through different platforms. The participants were requested to provide the trained experts with any changes regarding menstrual cycles after each dose of the vaccine up to 6 months after the booster shots. The disturbances related to the vaccines were identified by the adverse events committee to find possible associations with the applied vaccines. Of 308 women who participated until the end of the study, 22 (7.1%) complained about at least one abnormality in their menstrual patterns. The most common disturbance was metrorrhagia as 10 (48%) incidences followed by menorrhagia as 6 events (24.2%). Notably, the identified complaints were persistent in 59% of the patients. In addition, 14 studied cases developed COVID-19 infection after menstrual disorders. In these cases, COVID-19 could also play a role in the persistence of postvaccine menstrual disturbances. COVID-19 vaccination could affect menstrual cycle in women with no remarkable previous medical history. More longitudinal studies are required regarding this issue.